Chronic Pain following Chest Trauma: Prevalence, Associated Factors, and Psychosocial Impact - Mohamed Kahloul; Imene Kacem; Mohamed Mehdi Sboui; Olfa El Maalel; Hana Daami; Meriam Hafsia; Manel Limam; Sana Aissa; Imene Ben Kbaier; Nejib Mrizak; Ajmi Chaouch; Walid Naija (Pain Research and Management)
Background. Chronic pain (CP) is a real public health concern. It is a common cause of poor quality of life and workplace absenteeism. It is well studied in many medical and surgical fields. However, only few data are available as regards to its occurrence in trauma patients. Purpose. To assess the prevalence, associated factors, and psychosocial impact of CP following chest trauma. Methods. This is an observational, descriptive, and analytic cross-sectional study performed in a Tunisian department of anesthesia and intensive care over a two-month period. Adult patients admitted one year ago for isolated chest trauma were enrolled. Data were collected by a phone interview. Studied variables were sociodemographic characteristics, traumatic injuries and their management, the occurrence of CP, and its psychosocial impact. CP was diagnosed by the Brief Pain Inventory (BPI) considering an evolution period of at least 3 months. Its impact was assessed by the BPI and the Posttraumatic stress disorder Checklist Scale (PCLS). Results. Fifty-four patients were included in the study. The prevalence of CP was 79.6%. The average CP intensity was 3.18 ± 1.4. It was neuropathic in 90.7%. Its main associated factors were pleural effusion (p=0.016), time to ICU admission (p=0.05), and posttraumatic stress disorders (p=0.017). After a multivaried analysis, only pleural effusion was associated with CP (p=0.01, OR = 6.9 CI 95% [1.2–37.3]). Probable or very likely PTSDs were noted, respectively, in 10 and 9 cases. Regarding the psychosocial impact of CP, the most commonly affected dimensions were general activity, work, sleep, and mood. Conclusion. CP following chest trauma is frequent and severe requiring preventive measures such as high risk patients screening, better management of acute pain, and a multidisciplinary approach for patients with diagnosed CP.